Improving the Genetics of Tuber Yield and Resistance to Mite to Avoid Mite Incident and to Increase the Productivity of Cassava (Manihot esculenta Crantz) - null Sholihin; Sri W. Indiati; Kartika Noerwijati; Tinuk S. Wahyuni; Heru Kuswantoro; null Suhartina; Rudy Soehendi; Marida S. Y. I. Bayu; Gatut W. A. Sutanto; Made J. Mejaya; Rohmad Budiono (Scientifica)
Mite (Tetranychus urticae) that attacks the cassava plants during dry season can reduce the yield up to 53%, depending on plant age and duration of attacks. The objective of the trial was to evaluate the cassava promising clones for tuber root yield and mite resistance. The field trial was done in Malang, East Java, Indonesia, in 2018 with fifteen clones using a randomized complete block design, with three replications. The glass house experiment for mite evaluation was done in Malang in 2018. A total of fifteen clones were used in this glass house trial. Infestation of mite (imago) was done 1 month after plating with 15 mites/pot on the lower part of the fourth or fifth leaf. Results of the field experiment showed that there was a genetic variability in the clones tested. The fresh tuber yield in 10 months ranged 30.33–55.67 t/ha with mean 41.34 t/ha. The fresh tuber yield of clone OMM 0915-11 was the highest of 55.67 t/ha. The tuber result of clone UJ5d50-207-3 similar to OMM 0915-11 and significantly higher than check variety UJ5. Response of clones to mite attack were as follows: two clones were resistant, ten clones were moderately resistant, and the other clones were susceptible. Based on the green house trial, the response of clones to mite attack was as follows: one clone was highly resistant, two clones were resistant, ten clones were moderately resistant, and the other clones were susceptible. Clone OMM 0915-11 was resistant variety or high resistant variety based on the green house and field experiments, while clone UJ5d50-207-3 was moderately resistant based on both glass house and field experiments.